Can a knee brace reduce the strain in the anterior cruciate ligament? A study using combined in vivo/in vitro method. (June 2016) - Hangalur, Gajendra; Brenneman, Elora; Nicholls, Micah; Bakker, Ryan; Laing, Andrew; Chandrashekar, Naveen
Background and aim: It is unknown whether prophylactic knee braces can reduce the strain in the anterior cruciate ligament during dynamic activities. Technique: An athlete, who had characteristics of high anterior cruciate ligament injury risk, was chosen. A motion capture system (Optotrak Certus; Northern Digital, Waterloo, ON, Canada) was used to record dynamic trials during drop-landing activity of this subject with and without the knee brace being worn. A musculoskeletal model was used to estimate the muscle forces during this activity. A dynamic knee simulator then applied kinematics and muscle forces on a cadaver knee with and without the brace mounted on it. The anterior cruciate ligament strain was measured. Discussion: The peak strain in the anterior cruciate ligament was substantially lower for the braced (7%) versus unbraced (20%) conditions. Functional knee braces could decrease the strain in the anterior cruciate ligament during dynamic activities in a high-risk subject. However, the reduction seems to be a result of altered muscle firing pattern due to the brace. Clinical relevance: Prophylactic knee brace could reduce the strain in the anterior cruciate ligament of high-risk subjects during drop-landing through altered muscle firing pattern associated with brace wear. This could help reduce the anterior cruciate ligament injury risk.